The Role of Market Orientation and Creativity in Affecting the Marketing Performance of Market Traders in Aceh Market Banda Aceh City - Marlizar, Marlizar; Harahap, Taufik Hidayat; Alda, Mirjan Fajri; Marwiadi, Marwiadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze the effect of market orientation and creativity on marketing performance in apparel traders in the Aceh Market in Banda Aceh City. The research sample of 96 respondents with accidental sampling sampling technique. Data collection techniques used were observation and questionnaires. The data analysis technique used multiple linear regression analysis and was treated with the help of SPSS software version 22.0. The results showed that partially market orientation and creativity variables influenced marketing performance. While the creativity variable has no effect. This means that the higher the market orientation will improve marketing performance. Simultaneously market orientation and creativity play a role in marketing performance improvement. To improve marketing performance in Aceh market traders, traders are required to be more creative in marketing their merchandise. The recommendations for further research are expected to be able to add variables such as innovation, competitive advantage, and marketing strategies.